Soil bacterial community changes along elevation gradients in karst graben basin of Yunnan-Kweichow Plateau - Li, Qiang; Qiu, Jiangmei; Liang, Yueming; Lan, Gaoyong (Frontiers in Microbiology, 2022)
Elevation gradients could provide natural experiments to examine geomorphological influences on biota ecology and evolution, however little is known about microbial community structures with soil depths along altitudinal gradients in karst graben basin of Yunnan-Kweichow Plateau. Here, bulk soil in A layer (0~10 cm) and B layer (10~20 cm) from two transect Mounts were analyzed by using high-throughput sequencing coupled with physicochemical analysis. It was found that the top five phyla in A layer were Proteobacteria, Acidobacteria, Actinobacteria, Bacteroidetes and Verrucomicrobia, and the top five phyla in B layer were Proteobacteria, Acidobacteria, Actinobacteria, Verrucomicrobia and Chloroflexi in a near-neutral environment. Edaphic parameters were different in two layers along altitudinal gradients. Besides that, soil microbial community compositions varied along altitudinal gradient, and soil organic carbon (SOC) and total nitrogen (TN) increased monotonically with increasing elevation. It was further observed that Shannon indexes with increasing altitudes in two transect Mounts decreased monotonically with significant difference (P=0.001), however beta diversity followed U-trend with significant difference (P=0.001). The low proportions of unique operational taxonomic units (OTUs) appeared at high altitude areas which impact the widely accepted elevation Rapoport's rules. The dominant Bradyrhizobium (alphaproteobacterial OTU 1) identified at high altitudes in two layers constitute the important group of free-living diazotrophs and could bring fixed N into soils, which simultaneously enhances SOC and TN accumulation at high altitudes (P<0.01). Due to different responses of bacterial community to environmental changes varying with soil depths, altitudinal gradients exerted negative effects on soil bacterial communities via soil physical properties and positive effects on soil bacterial diversities via soil chemical properties in A layer, however the results in B layer were opposite. Overall, our study is the first attempt to bring a deeper understanding of soil microbial structure patterns along altitudinal gradients at karst graben basin areas.